Utilizing student generated writing on wiki platform to enrich Malay literature content on built environment - Asif, Nayeem; Utaberta, Nangkula (Global Academic Excellence (M) Sdn Bhd, 2018)
This paper describes the procedure of engaging students in producing collaborative writing and utilizing the online platform to build up a database of written content on specific discipline using the student-generated writings. The aim is to add up to the content on built environment in the Malay language as professional and academicians report a scarcity in this field. The process involves thirty-three third-year students of architecture as the primary participants to produce writings based on a given template and three postgraduate students to review and comment on the writings for maintaining a standard quality. 24 articles were selected after the screening process and uploaded to a wiki platform named Wikia under the title of WARIS ARKIPEDIA. Continuation of this process with additional batches of student can add up more articles in the existing database. It is expected that once available online, user's participation can effectively improve the content quality as well as add-on more related wikis and contribute to building up a national architecture literature database in the Malay language.